The small East African shorthorn zebu cows in Kenya. I: linear body measurements - Mwacharo, Joram M.; Okeyo Mwai, Ally; Kamande, G.K.; Rege, J.E.O. (Springer, 2006)
Assessment of genetic diversity is a prerequisite for the management and conservation of animal genetic resources. Appropriate design of breeding programmes is therefore impossible for breeds that have not been adequately characterized either phenotypically and/or genetically. Phenotypic characteristics are important in breed identification and classification in ways that farming communities can relate with. This study phenotypically characterized two breeds of zebu cattle in Kenya. A total of 12 measurements (face length, ear length, horn length, heart girth, height at withers, chest depth, body length, height at rump, pelvis width, corpus length, pin bone width and tail length) were collected on 373 Maasai and 277 Kamba zebu kept by traditional farmers in south-east Kenya. The data were classified on the basis of breed group, age group, sex and coat colour pattern. Breed group, age group and sex significantly influenced all measurements. Coat colour pattern significantly influenced only height at withers, corpus length, ear length and tail length. Except for horn and ear length, all the other measurements were significantly higher for the Maasai zebu. Additionally, the Maasai zebu was taller than it was long. The opposite was true for the Kamba zebu. The Maasai and Kamba zebus can be classified as medium-sized breeds; however, great variations exist in their body sizes within and between the breeds.